2018
DOI: 10.21512/lc.v12i2.3745
|View full text |Cite
|
Sign up to set email alerts
|

“Wait, How Do I Say that in English?” Communication Strategies for English as a Foreign Language Learners

Abstract: This research aimed to investigate communication speaking skill strategies applied by two groups of English foreign language learners in two boarding senior high schools in Aceh, Indonesia. Of the successful group, there were 52 learners and of the less successful group 24 learners. To collect the data, this study employed the observation sheet adapted by Tarone(1978), which determined nine categories of communication strategies; approximation, word coinage, circumlocution, literal translation, language switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Generally, they employed communication strategies because of thinking time, avoiding nervousness, avoiding hesitation, overcoming the lexical deficiency of the target language, avoiding knowledge gap, justification, emphasizing the intended meaning, overcoming communication breakdowns. Several studies have justified those findings above (Al-Gharaibeh, 2016;Aziz et al, 2018;Dewi et al, 2018;Jumiati et al, 2017;Nizar et al, 2018;Nugroho, 2019;Saidah et al, 2020;Syahri, 2009a).…”
Section: Direct Appeal For Helpmentioning
confidence: 79%
See 1 more Smart Citation
“…Generally, they employed communication strategies because of thinking time, avoiding nervousness, avoiding hesitation, overcoming the lexical deficiency of the target language, avoiding knowledge gap, justification, emphasizing the intended meaning, overcoming communication breakdowns. Several studies have justified those findings above (Al-Gharaibeh, 2016;Aziz et al, 2018;Dewi et al, 2018;Jumiati et al, 2017;Nizar et al, 2018;Nugroho, 2019;Saidah et al, 2020;Syahri, 2009a).…”
Section: Direct Appeal For Helpmentioning
confidence: 79%
“…Additionally, the study carried out by (Aziz et al, 2018) distinguished between successful and unsuccessful students, and they found that roughly three communication strategies were not employed for both successful and unsuccessful students, namely circumlocution, word coinage, and mime strategies. Regarding this study, it was found that the absence of some communication strategies occurred in this research as well, and among others are circumlocution, word coinage, and mime strategies.…”
Section: Direct Appeal For Helpmentioning
confidence: 99%
“…Students prefer to use other strategies to solve their problems than using this strategy. Aziz et al, (2018) stated that the students describe the characteristics or elements of an object or action instead of using the appropriate target language item. The fourth is approximation.…”
Section: Finding and Discussionmentioning
confidence: 99%